Differential action of NMDA antagonists on cholinergic neurotoxicity produced by N-methyl-D-aspartate and quinolinic acid. - Pawley, A. C. (1996)
1. Injections of N-methyl-D-aspartate (NMDA) and quinolinic acid (Quin), agonists that activate NMDA receptors, into the rat nucleus basalis magnocellularis (nbM) produced a dose-related decrease in cholineacetyltransferase (ChAT) activity in the cerebral cortex and amygdala 7 days after injection. 2. In order to examine the possibility that NMDA and Quin activate different sub-types of NMDA receptors to produce central cholinergic neurotoxicity, the sensitivity of these agonists to the action of three different NMDA receptor antagonists, 2-amino-7-phosphonoheptanoate (AP-7), 7-chlorokynurenate and dizolcipine (MK801) was examined by injecting a fixed dose of NMDA (60 nmol) or Quin (120 nmol) in combination with different doses of the antagonists into the nbM. 3. Both AP-7 (0.6-15 nmol) and 7-chlorokynurenate (3.75-200 nmol), which block the NMDA receptor recognition site and glycine modulatory site respectively, produced a dose-related attenuation of the NMDA or Quin-induced decrease in ChAT activity in both the cortex and amygdala. Both antagonists showed a greater potency against the action of NMDA than against Quin. 4. MK801 (2-200 nmol), an NMDA receptor-linked channel blocker, attenuated the Quin and NMDA response only at a high dose. Unlike AP-7 and 7-chlorokynurenate, MK801 did not exhibit a consistent difference in its potency as an antagonist against NMDA and Quin. 5. The differential antagonist actions of AP-7 or 7-chlorokynurenate against NMDA and Quin-induced cholinergic neurotoxicity suggest that the excitotoxic actions of these two agonists are mediated via distinct NMDA receptor sub-types. The NMDA- and Quin-sensitive receptors appear to differ with respect to properties of the receptor recognition and glycine modulatory sites that are associated with these receptors.